Deixis and Its Function in the Novel Imra'ah 'Inda Nuqṭah Al-Ṣifr by Nawāl Al-Sa'dāwī: A Pragmatics Study - Jauharatus Shufiyyah; Susanti, Rina (Islah: Journal of Islamic Literature and History, 2023)
This paper aims to describe the types of deixis and their function in the novel Imra‘ah ‘Inda Nuqṭah Al-Ṣifr (abbreviated as IINA) by Nawal Al-Sa’dawi. The method used is a qualitative method with a library research design. The data collection stage uses the note-taking method. As for the data analysis technique, it uses descriptive analytic of utterances that contain deixis in the novel, then analyzes its function. The findings of the study show that they are five types of deixis in the IINA novel, which include persona, time, place, discourse, and social deixis. In persona deixis, 60 data were found, consisting of 30 first persona data, 15 second persona deixis data, and 15 third persona deixis data. There are 7 data for time deixis, 8 data for place deixis, 4 discourse deixis and 5 data for social deixis. On the other hand, the function of deixis shows that persona deixis functions as a reference for people or characters in the story or refers to pronouns in the first person (speaker), second (opposite0, or third (person being talked about). Time deixis serves as an indication of the time of events that have taken place, are taking place, and will take place. Place deixis serves as a reference for places that are close to the speaker or places far from the speaker. Meanwhile, discourse deixis functions as explaining something that has been discussed or something that will be discussed. Finally, social deixis serves to show differences in social class between speakers and interlocutors and maintains the value of decency in society.